2021
DOI: 10.3389/fpsyg.2021.743936
|View full text |Cite
|
Sign up to set email alerts
|

Online Learning Satisfaction During COVID-19 Pandemic Among Chinese University Students: The Serial Mediation Model

Abstract: The aim of this study was to investigate the relationship between interaction and online learning satisfaction, whether this relationship is mediated by academic self-efficacy and student engagement among Chinese university students during the COVID-19 pandemic. A serial mediation model was developed to examine the proposed relationship. This study employed a cross-sectional, questionnaire-based research design. A sample of 1,504 Chinese university students (Mage=19.89years, SDage=1.93) from five provinces in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
86
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 123 publications
(135 citation statements)
references
References 112 publications
8
86
0
3
Order By: Relevance
“…What’s more, some other learner-related factors have been found in affecting OLS, such as student engagement ( Gao et al, 2020 ; Han et al, 2021 ; She et al, 2021 ; Sinval et al, 2021 ), learner-learner interaction ( Skinner et al, 2008 ; Kurucay and Inan, 2017 ), learner-instructor interaction (which is to be discussed in the following section), learner’s interaction with content ( Knowles et al, 2020 ; Kim and Kim, 2021 ). What is noteworthy is the large scale study conducted by Li et al (2016b) .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…What’s more, some other learner-related factors have been found in affecting OLS, such as student engagement ( Gao et al, 2020 ; Han et al, 2021 ; She et al, 2021 ; Sinval et al, 2021 ), learner-learner interaction ( Skinner et al, 2008 ; Kurucay and Inan, 2017 ), learner-instructor interaction (which is to be discussed in the following section), learner’s interaction with content ( Knowles et al, 2020 ; Kim and Kim, 2021 ). What is noteworthy is the large scale study conducted by Li et al (2016b) .…”
Section: Resultsmentioning
confidence: 99%
“…It was revealed that learner-instructor interaction and learner-content interaction were significantly predictive of student OLS but learner-learner interaction was not. And She et al (2021) took a cross-sectional, questionnaire-based investigation of 1,504 Chinese university students and found a significant positive relationship between learner-instructor interaction and OLS. It was also revealed that learners’ self-efficacy and engagement serial mediated the relationship between learner-instructor interaction and OLS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The learning satisfaction is analyzed by Zeng and Wang (2021) for the synchronous and asynchronous elements of online course design. She et al (2021) investigated the relationship between interaction and online learning satisfaction. A similar study by Gopal et al (2021) identifies course design as one of the factors, which may affect learners' satisfaction.…”
Section: Learning Satisfactionmentioning
confidence: 99%
“…Self-efficacy can be defined as the confidence in one's ability to perform certain learning tasks in the long term of the e-learning process or to complete tasks in the right time frame (Li et al, 2012 ; Haq et al, 2022 ; Muliati et al, 2022 ). It has been more concerned with e-learning and continuance intention (Chang et al, 2020 ; She et al, 2021a , b , 2022 ; Calaguas and Consunji, 2022 ; Sulaymani et al, 2022 ).…”
Section: Theoretical Development and Hypothesesmentioning
confidence: 99%